Corporate Crime: The Firm As Victim and Offender - Galvin, Miranda A. (Advances in Criminological Theory Series, 2025)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Table of Contents -- Contributors -- Preface -- Part I: Setting the Stage: Crime and Theories of the Firm -- 1. Moral Responsibility and Theories of the Firm -- 2. Corporate Criminal Liability and the Purposes of Punishment -- 3. Some Reflections on the "Corporate Offender" in Criminal Law -- Part II: Corporate Victimization -- 4. What Do We Owe the Victims of Corporate Crime? -- 5. Corporate Crime, Capture, and the Opioid Crisis -- 6. Corporate Crime Victimization in the Gambling Industry -- 7. Weaving Webs of Compliance: Integrating Vertical and Horizontal Prevention of Corporate Involvement in Human Rights Violations -- Part III: Corporate Offending -- 8. Applying the Opportunity Perspective to Corporate Offending and Victimization -- 9. Corporate Wrongdoing and Shareholders -- 10. Patterns of Corporate Life-Course Offending -- 11. Structure, Agency, and the Role of the State in Corporate Crime: Negotiating Current and Contemporary Challenges to Human Safety -- Afterword: Corporate Criminal Justice -- Index.